Guilt Trips in Gone Girl Novel by Gillian Flynn (2012) - El Ardhi, Rafiqa Hanif; Anwar, Desvalini (English Language and Literature, 2023)
This research analyzes the novel Gone Girl by Gillian Flynn (2012). The main problem analyzed is the guilt trips that happen in the married life of the main characters in the novel Gone Girl by Gillian Flynn. This research uses the psychoanalysis theory by Sigmund Freud to expose the meaning of the novel.  This research uses a descriptive qualitative method and the data will be taken from words, phrases, and statements from the novel as the centered data. The aims of the analysis are to reveal how guilt trips are committed by the female character in the Gone Girl novel by Gillian Flynn, to uncover the type of guilt trips committed by the female main character, and to expose how the male main character overcomes guilt trips. The findings reveal the reasons why guilt trips happen, the forms, and the responses to the guilt trips. Furthermore, the causes of guilt trips are emotional dependency, the power to manipulate, and low self-esteem and insecurity. Then, it exposes three types of guilt trips there are societal, victimhood, and ethical guilt trips. Lastly, the victim who gets guilt-tripping in the novel responds to the guilt trips by recognizing the manipulation, expressing the emotion, as well as offering sympathy.